Territorial differences in living standards in Uzbekistan - Kurbanov Bekmetovich, Shukhrat; Oteuliev Orinbayevich, Medetbay (Quaestiones Geographicae, 2021)
The concepts of ‘standard of living’, ‘quality of life’ and ‘lifestyle’ are analysed in a comparative manner. The author has made a rating assessment of the regions of the Republic in terms of living standards based on a set of 10 statistical indicators. As a result, regions of Uzbekistan with a relatively high and relatively low standard of living were identified.